2010
DOI: 10.1021/ct1003803
|View full text |Cite
|
Sign up to set email alerts
|

Excited States in Solution through Polarizable Embedding

Abstract: We present theory and implementation of an advanced quantum mechanics/molecular mechanics (QM/MM) approach using a fully self-consistent polarizable embedding (PE) scheme. It is a polarizable layered model designed for effective yet accurate inclusion of an anisotropic medium in a quantum mechanical calculation. The polarizable embedding potential is described by an atomistic representation including terms up to localized octupoles and anisotropic polarizabilities. It is generally applicable to any quantum che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
597
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 321 publications
(614 citation statements)
references
References 64 publications
(158 reference statements)
10
597
0
Order By: Relevance
“…It has previously been demonstrated that the RMSD from QM ESPs decreases almost as sharply for ESP-fitted charges as for a charge distribution with multipoles up to quadrupoles or octopoles. 5,17,19 The observation that the error in the ESP decreases sharply with the distance at which it is evaluated will be taken advantage of in the next section.…”
Section: Molecular Electrostatic Potentials Of the Solvent Moleculesmentioning
confidence: 99%
“…It has previously been demonstrated that the RMSD from QM ESPs decreases almost as sharply for ESP-fitted charges as for a charge distribution with multipoles up to quadrupoles or octopoles. 5,17,19 The observation that the error in the ESP decreases sharply with the distance at which it is evaluated will be taken advantage of in the next section.…”
Section: Molecular Electrostatic Potentials Of the Solvent Moleculesmentioning
confidence: 99%
“…This article focuses on the perspectives of recent developments within the polarizable embedding (PE) method, [1] which is a multiscale approach developed over the last years. Similar methods, such as the effective fragment potential method, [2] have focused mainly on relative energies and molecular geometries, whereas the PE method has its primary focus on molecular response properties as well as spectroscopic constants.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of diffuse functions in the first excitation of the water molecule was previously highlighted [101]. We chose a 6-31++G* basis set [118][119][120], meaning that DMRG (10,30)[512] corresponds to the active space of a full configuration interaction (FCI) calculation. However, although this small basis set will not yield accurate results, it is a suitable choice here as it permits us to carry out a FCI-type DMRG calculation that does not require further consideration of dynamical correlation effects.…”
Section: Computational Methodsologymentioning
confidence: 99%
“…The PE scheme [29,30] divides the environment into (molecular) fragments. We associate to each of these fragments a set of electrostatic multipoles, usually localized at the atomic centers [85].…”
Section: Polarizable Embeddingmentioning
confidence: 99%
See 1 more Smart Citation